Noncoding RNAs: the crucial role of programmed cell death in osteoporosis - Han, Juanjuan; Zhu, Yuqing; Zhang, Jiale; Kapilevich, Leonid; Zhang, Xin-an (Frontiers in Cell and Developmental Biology, 2024)
Osteoporosis is the most common skeletal disease characterized by an imbalance between bone resorption and bone remodeling. Osteoporosis can lead to bone loss and bone microstructural deterioration. This increases the risk of bone fragility and fracture, severely reducing patients' mobility and quality of life. However, the specific molecular mechanisms involved in the development of osteoporosis remain unclear. Increasing evidence suggests that multiple noncoding RNAs show differential expression in the osteoporosis state. Meanwhile, noncoding RNAs have been associated with an increased risk of osteoporosis and fracture. Noncoding RNAs are an important class of factors at the level of gene regulation and are mainly involved in cell proliferation, cell differentiation, and cell death. Programmed cell death is a genetically-regulated form of cell death involved in regulating the homeostasis of the internal environment. Noncoding RNA plays an important role in the programmed cell death process. The exploration of the noncoding RNA-programmed cell death axis has become an interesting area of research and has been shown to play a role in many diseases such as osteoporosis. In this review, we summarize the latest findings on the mechanism of noncoding RNA-mediated programmed cell death on bone homeostasis imbalance leading to osteoporosis. And we provide a deeper understanding of the role played by the noncoding RNA-programmed cell death axis at the gene regulatory level of osteoporosis. We hope to provide a unique opportunity to develop novel diagnostic and therapeutic approaches for osteoporosis.